Revenue and Expenditure Structure of Vyas Municipality (Journal of Nepalese Business Studies, 2018)
The local governments or the municipalities are responsible to provide administrative services to the local level and to develop infrastructures to provide physical facilities to municipal people. Thus, the major functions of the municipalities are the building up the infrastructure and supra structure and protecting public places and so on. To conduct such philanthropic works it is essential to sustain themselves financially. This study has intense relation with revenue and expenditure of Vyas Municipalities regarding the objectives to analyze, examine and interpret the Revenue and Expenditure. Descriptive research design has been adopted to conduct present study. Under the descriptive research design this study focuses on analyzing income and expenditure pattern of Vyas municipality thus case study approach has been followed to conduct this research. There are 243 municipalities in Nepal which are considered as the population of this study. Among them Vyas municipality is taken as sample using convenience sampling method. This study focuses on municipal revenue and expenditure thus based on secondary data. Vyas municipality largely depends upon the revenue raised from external sources to fulfill the financial requirements. The total revenue has been occupied by internal revenue and external revenue. The average growth rate of internal revenue has been greater than external revenue during the study period. Vyas municipality itself has been suffering from financial inadequacy. So unnecessary expenditure made for the consumption purpose should be cut off. Expenditure made for unproductive sectors should be minimized and utilized effectively. The Journal of Nepalese Business Studies Vol. X No. 1 December 2017, Page: 42-55